Arcana Academy - Kova, Elise (Kova, Elise. Arcana Academy series, 2025)
"Clara Graysword has survived the underworld of Eclipse City through thievery, luck, and a whole lot of illegal magic. After a job gone awry, Clara is sentenced to a lifetime in prison for inking tarot cards--a rare power reserved for practitioners at the elite Arcana Academy. Just when it seems her luck has run dry, the academy's enigmatic headmaster, Prince Kaelis, offers her an escape--for a price. Kaelis believes that Clara is the perfect tool to help him steal a tarot card from the king and use it to re-create an all-powerful card long lost to time. In order to conceal her identity and keep her close, Kaelis brings Clara to Arcana Academy, introducing her as the newest first-year student and his bride-to-be. Thrust into a world of arcane magic and royal intrigue, where one misstep will send her back to prison or worse, Clara finds that the prince she swore to hate may not be what he seems. But can she risk giving him power over the world--and her heart? Or will she take it for herself?"--